Development of food safety capability in Ghana to enhance access to the Global Food Manufacturing Value Chain (GFMVC) - Mensah, L. D. (Cranfield University, 2011)
Demonstrating compliance with food safety requirements of the global economy is a prerequisite for access. As tariff barriers diminish, developing countries are exposed to greater opportunities for repositioning their food manufacturing sectors in global value chains (GVCs). At the same time, the measures for the protection of public health and safety are becoming more stringent because of the series of food safety crises that characterised the global food value chain in the 1980s and 1990s, and that still linger on. The new demands arising from the need to protect consumer safety, coupled with the structure of the global economy have introduced new challenges for developing countries in terms of accessing the global food manufacturing value chain(GFMVC) with manufactured products. This is the case for the Ghanaian food manufacturing sector. Therefore, this study aims to understand the practice of developing food safety capability to enhance access to the GFMVC using high value added products, to identify performance gaps in the Ghanaian context and propose an appropriate framework (legal, institutional and policy) to address the major gaps, while meeting the basic requirements of food safety. A multiple case study methodology was adopted, using the UK food and drinks sector as a benchmark for the Ghanaian food manufacturing sector. The main techniques employed for data collection were surveys, interviews and content analysis. Based on the findings and insights gathered from the investigation, a technical regulation based on Hazard Analysis and Critical Control Point (HACCP) is proposed as a means to enhance the compliance of enterprises in Ghana with the basic requirements of food safety. Because of the current lack of capability at the national and enterprise level, a four-phase implementation plan is recommended to progressively ease enterprises into mandatory compliance with integrated food safety management systems. The study also recommends that the current multiple agency structure is maintained, however, mandates, roles and responsibilities, and jurisdictions need to be clarified, and values reformed. Various kinds of support (e.g. funds, training) also have to be provided to enterprises to facilitate their compliance and enhance their access to the GFMVC.
Keywords: Food manufacturing; food safety; international trade; regulation; Ghana